ANALISIS KONSUMSI BAHAN BAKAR MOTOR BENSIN YANG TERPASANG PADA SEPEDA MOTOR SUZUKI SMASH 110CC - Ferdywanto Parende; Hardi Gunawan; I Nyoman Gede (JURNAL POROS TEKNIK MESIN UNSRAT, 2012)
This research aims to determine the fuel consumption of gasoline engine mounted on a 110cc Suzuki Smash. The data taken on the motorcycle in different gear ratios and speed for a travel distance of 2.5 km.Analysis was conducted on gear ratios 2, 3 and 4 at speeds of 20, 25, 30, 35, and 40 km / h. Observations and calculations for the arrays of indicate that fuel consumption on gear ratio 2 is 359.2, 410.9, 439.0, 545.9, and 648.9 g / h respectively. At gear ratio 3 is 296.9, 295.8, 408.6, 494.4 and 624.5 g / h respectively. At gear ratio 4 is 201.9, 249.4, 412.0, 330.8 and 538.0 g / h respectively. It is concluded that the higher the speed of the motor, the greater the rate of consumption of fuel.From the observation it was found that the test was performed at the engine rotation of 2136 to 6182 rpm. Results demonstrate that at the speed of 20 km / h to 40 km / h it is more efficient operate with gear ratio 4.Keywords: Fuel Consumption, Gasoline Motor, Suzuki Smash 110cc.